Killer whales, Orcinus orca (Artiodactyla: Delphinidae) in Guatemala: sighting records, photographic match, and interaction with Bryde’s whales, Balaenoptera edeni (Artiodactyla: Balaenoptera) - Ortiz-Wolford, Jenniffer; Romero, Julio C.; Cabrera, Andrea A. (Revista de Biología Tropical, 2023)
Introduction: Killer whales (Orcinus orca) have a global distribution, but many low-latitude populations such as the Eastern Tropical Pacific are not well studied. Objective: Provide a review of killer whale sightings in the Exclusive Economic Zone of the Pacific of Guatemala, for which there has previously been little information. Methods: We reviewed national and regional publications, as well as anecdotal records of killer whale sightings in Guatemala. Results: We document five sightings spanning three decades (1990-2020). Four sightings were recorded between 2010 and 2020 and occurred within the San José Canyon or over the continental shelf. Group size varied from 1-15 individuals (x: 6 ± 4.3). We report a photographic match of three killer whale individuals from a single pod previously sighted in Cabo Corrientes, México, 11 years and 1 778 km apart. We also describe an interaction between a killer whale pod and two adult Bryde’s whales (Balaenoptera edeni), in which the Bryde’s whales followed a female killer whale and its calf. Conclusions: This study represents a contribution to the knowledge of killer whales in the region. It highlights the importance of data collection from both scientific and anecdotal records and supports the need of establishing national and regional monitoring and conservation programs for cetaceans.